Health Care-Associated Staphylococcus aureus Pneumonia - Duncan Webster; Linda Chui; Gregory J Tyrrell; Thomas J Marrie (Canadian Journal of Infectious Diseases and Medical Microbiology)
INTRODUCTION: While Staphylococcus aureus is an uncommon but serious cause of traditional community-acquired pneumonia (CAP), it is a predominant cause of nosocomial pneumonia in addition to the unique clinical entity of health care-associated pneumonia (HCAP). A cohort of bacteremic S aureus pneumonia cases was reviewed to determine the role of HCAP among the cohort, and to assess for differences between CAP and HCAP.